Pemberdayaan Perempuan Pedesaan dengan Pendekatan Participatory Action Research: Produksi Sabun Cuci Piring Herbal Rumahan - Suryaneta Suryaneta; Kiki Yuli Handayani; Amelia Sri Rezki; Achmad Gus Fahmi; Iwan Syahjoko Saputra (Riau Journal of Empowerment, 2022)
This article aimed to do research on the economic empowerment of rural women using Participatory Action Research approach. PAR required performing research to define a problem or implement information as solutions to problems that have been defined. PAR is "research by, with, and for people" as opposed to "research on person." Participatory action research is participatory in the sense that it is a necessary condition that people play a key role and have relevant information about the existing social system (community) under review, and that they participate in the design and implementation of the action plan based on the findings of the research. This research was preceded in the search for problems faced by women in Jatisari Village, Lampung Province. The solutions obtained were in the form of providing knowledge, entrepreneurial skills, and examples of how to produce innovative products by utilizing the natural resources around them. Empowerment activities include three stages, namely: (1) Providing counseling about the possible benefits of natural resources in the environment as products for women’s needs by providing examples of the use of plants that are easy to obtain and grow, for example aloe vera which is easily found in the yard to produce a product; (2) Provide counseling on how to become a woman entrepreneur and analyze household products with high demand for daily needs (eg liquid dish soap); and (3) Demonstrating how to use aloe vera as a component in the manufacture of liquid dish soap.